A decarbonization strategy for lattice girders in primary support: A case study in Wanrong tunnel on Meng-Hua railway - Feng Lu; Zhenyu Chen; Xianshun Zhou; Yingda Zhang; Wenge Qiu; Xinqiang Gao; Kai Liu (Case Studies in Construction Materials)
China faces an urgent need to reduce carbon emissions, and tunnel construction will play a critical role in achieving this goal. While much focus has been placed on new construction materials, the potential carbon emission reductions from structural optimization have been largely overlooked. This study addresses the issue of overdesign in tunnel lattice girders (LG) and achieves two key outcomes: preventing overdesign while ensuring tunnel safety, and demonstrating the decarbonization potential and economic benefits of optimizing the LG structure. The LG overdesign was found to stem from an overestimation of loose soil load in Chinese regulations. After accounting for the resistance of surrounding rock, mechanical evaluations revealed that the main steel bars near the rock side, diagonal bars, welds, and stirrups contribute minimally to the load-bearing capacity of the LG. An optimization strategy was proposed, involving adjustments to the diameters of the main steel and diagonal bars, the reduction of weld lengths, and the elimination of stirrups. On-site experiments conducted in the Wanrong tunnel of the Meng-Hua railway confirmed the safety of the optimized design and demonstrated a 36.77 % reduction in carbon emissions, amounting to 3462.85 tons, with a decrease of 0.4849 t/m in carbon emission intensity compared to standard designs. Further emission analysis considered quantities, contributing factors, construction stages, and individual components. Compared to the traditional scheme, the optimized solution has reduced the total project cost by 36.76 %. The decarbonization strategy proposed in this study provides a possible solution for future tunnel constructions.